2020
DOI: 10.1177/1098612x20949038
|View full text |Cite
|
Sign up to set email alerts
|

Feline conjunctival microbiota in a shelter: effects of time, upper respiratory disease and famciclovir administration

Abstract: Objectives The aim of this study was to evaluate changes in the conjunctival microbiota of shelter-housed cats with time, upper respiratory disease (URD) and famciclovir administration. Methods Cats were assigned to treatment groups on shelter entry. Healthy cats or cats with URD received ~30 mg/kg or ~90 mg/kg of famciclovir or placebo PO q12h for 7 days, or were untreated. Swabs were collected from ventral conjunctival fornices prior to (day 1) and immediately after (day 8) the treatment period. Microbiota a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The V4 region of the 16S rRNA gene was amplified using the modified 515F/806R amplicon primers as described by Walters et al 24 . Per sample, two PCR reactions and purifications were performed as described in Lucyshyn et al 25 . (Appendix ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The V4 region of the 16S rRNA gene was amplified using the modified 515F/806R amplicon primers as described by Walters et al 24 . Per sample, two PCR reactions and purifications were performed as described in Lucyshyn et al 25 . (Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…A negative control containing only reagents was performed for every 70 samples extracted to control for contamination from extraction kits. The V4 region of the 16S rRNA gene was amplified using the modified 515F/806R amplicon primers as described by Walters et al 24 Per sample, two PCR reactions and purifications were performed as described in Lucyshyn et al 25 (Appendix S1). Following the second purification, samples were quantified using a NanoDrop spectrophotometer (NanoDrop, Roche; Mississauga, ON, Canada).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Famciclovir, an orally administered prodrug of penciclovir, has been the subject of numerous investigations for the treatment of FHV-1 in cats. 4,5,8,74,78,[101][102][103][104] Several of these studies specifically utilized shelter-housed cats with IOSD 4,5,8,101 or animals in a 'foster' environment (temporary private residence). 102 Studies using experimental animals in a highly controlled laboratory setting have shown that famciclovir is an effective treatment for FHV-1 and that, at appropriate doses, anti-herpetic concentrations of penciclovir are achievable in the tear film.…”
Section: Famciclovirmentioning
confidence: 99%
“…102 Finally, although not specifically assessing drug efficacy, a study of shelter-housed cats treated with famciclovir concluded that the use of oral famciclovir given at 90 mg/kg q12h has minimal impact on the individual bacterial feline ocular surface microbiome. 101 When considered together, the existing clinical trials provide minimal evidence of famciclovir efficacy for treatment of feline IOSD in the shelter environment. Therefore, alternative strategies should currently be considered for shelter-housed cats with FHV-1 IOSD.…”
Section: Famciclovirmentioning
confidence: 99%
See 1 more Smart Citation